Etiology and patterns of mandibular fractures in cats - Castejón-González, Ana C.; Stefanovski, Darko; Reiter, Alexander M. (Frontiers in Veterinary Science, 2025)
IntroductionMandibular fractures resulting from maxillofacial trauma often require surgical intervention to promote proper bone healing. Understanding the etiology and patterns of mandibular fractures is crucial for selecting appropriate surgical treatment options. The objectives of this study were (1) to examine the etiology and location of mandibular fractures at and distal to the mandibular canine tooth and (2) to identify patterns and risk factors associated with these fractures in client-owned cats.MethodsMedical records and computed tomography (CT) scans of cats with at least one mandibular fracture located at or distal to the mandibular canine tooth were reviewed. The CT images of mandibles with ramus fractures were segmented and reconstructed into 3D models using the Mimics Innovation Suite (Materialise, Leuven, Belgium). These models were then printed in white or clear resin using an SLA 3D printer (Formlabs©) to identify fracture patterns.ResultsA total of 38 cats with 62 mandibular fractures were included in the study. The most common fracture location was the mandibular ramus (51.6%, excluding the condylar process), followed by the condylar process (33.9%). Fractures were often severely displaced and fragmented. The evaluation of the 3D-printed models identified three main patterns, which accounted for 75% of the fractures in the mandibular ramus. Fracture etiology was significantly associated with the pattern type (p = 0.028). Animal altercations were 9.3 times more likely to cause a pattern A fracture than an unknown cause.Discussion3D printing was useful for visualizing and describing the patterns of mandibular fractures in cats. Pattern A fractures were most commonly associated with animal altercations.